Ammonium chloride; as a mild and efficient catalyst for the synthesis of some 2-arylbenzothiazoles and bisbenzothiazole derivatives - Maleki, Behrooz; Salehabadi, Hafezeh (European Journal of Chemistry, 2010)
An efficient protocol has been developed for the preparation of a series of 2-arylbenzothiazoles derivatives from condensation of 2-aminothiophenol with aromatic aldehydes using ammonium chloride, which is a very inexpensive, metal-free and readily available reagent. The target compounds were obtained in good to excellent yields (58-92%) under fairly mild reaction conditions at room temperature.